CRITICIZING SPEECH ACT STRATEGIES IN BEAUTY VLOGGERS’ MAKEUP REVIEWS ON SOCIAL MEDIA: A SOCIOPRAGMATIC STUDY - Yosephine Marrietta Ardhya Yosani; FX Sawardi; Henry Yustanto (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2026)
This study aims to analyze the criticizing speech act strategies employed by beauty vloggers in makeup product reviews on social media. The research adopts a descriptive qualitative method with a sociopragmatic approach. The data consist of utterances containing criticizing speech acts produced by beauty vloggers in makeup review videos uploaded on YouTube and TikTok. The data sources were obtained from the channels of Affi Assegaf, Suhay Salim, Fatya Biya, Lifni Sanders, and Kiara Leswara, as well as the TikTok accounts of Reizuka Ari and Jovi Adhiguna. Data were collected by downloading the videos, transcribing the utterances orthographically, and classifying them based on Nguyen’s criticizing speech act strategies and Blum-Kulka’s speech act components. The findings reveal that beauty vloggers employ two major criticizing strategies, namely direct and indirect criticism. Direct criticism is expressed through explicit negative evaluations of product features, while indirect criticism is conveyed through mitigated expressions such as comparisons, suggestions, or compliments used as balancing devices. Furthermore, the criticism sequences demonstrate a recurring pattern consisting of pre-criticizing, main criticizing, and post-criticizing stages, which function to maintain politeness and interpersonal rapport in social media communication. These findings indicate that beauty vloggers strategically balance evaluative judgments and politeness considerations when delivering criticism to their audiences.